2015
DOI: 10.1002/bsl.2200
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Alterations Associated with War Trauma and Childhood Maltreatment

Abstract: Survivors of war trauma or childhood maltreatment are at increased risk for traumaspectrum disorders such as post-traumatic stress disorder (PTSD). In addition, traumatic stress has been associated with alterations in the neuroendocrine and the immune system, enhancing the risk for physical diseases. Traumatic experiences might even affect psychological as well as biological parameters in the next generation, i.e. traumatic stress might have transgenerational effects. This article outlines how epigenetic proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 176 publications
(201 reference statements)
0
27
0
2
Order By: Relevance
“…For instance, many chronically and severely abused children have PTSD that resolves after a period of time, but they continue to experience and be affected by long-term symptoms that result from the abuse but manifest in ways other than PTSD (De Bellis & Zisk, 2014;Patterson, Moniruzzaman, & Somers, 2014;Wayland, 2008). Moreover, the intergenerational transmission of trauma means that the offspring of a parent exposed to trauma may develop behavioral symptoms without direct exposure to a traumatic event (Ramo-Fernandez, Schneider, Wilker, & Kolassa, 2015;Yehuda & Bierer, 2009). Symptoms and functioning, rather than diagnostic criteria, have become the crucial question for forensic assessment as neuroscience revises the ways in which diagnostic categorization works (Casey, Oliveri, & Insel, 2014;Cuthbert, 2014).…”
Section: Multigenerational History and Epigeneticsmentioning
confidence: 99%
“…For instance, many chronically and severely abused children have PTSD that resolves after a period of time, but they continue to experience and be affected by long-term symptoms that result from the abuse but manifest in ways other than PTSD (De Bellis & Zisk, 2014;Patterson, Moniruzzaman, & Somers, 2014;Wayland, 2008). Moreover, the intergenerational transmission of trauma means that the offspring of a parent exposed to trauma may develop behavioral symptoms without direct exposure to a traumatic event (Ramo-Fernandez, Schneider, Wilker, & Kolassa, 2015;Yehuda & Bierer, 2009). Symptoms and functioning, rather than diagnostic criteria, have become the crucial question for forensic assessment as neuroscience revises the ways in which diagnostic categorization works (Casey, Oliveri, & Insel, 2014;Cuthbert, 2014).…”
Section: Multigenerational History and Epigeneticsmentioning
confidence: 99%
“…Childhood interpersonal trauma can have a detrimental impact on a child's development, especially regarding psychological and interpersonal functioning [35,36]. Their potentially adverse consequences on the psychological sphere are manifold: increased risk of depression, anxiety, posttraumatic stress symptoms, aggression, dissociation, substance use, risky sexual behaviors, as well as borderline, antisocial, schizotypal, avoidant, and schizoid personality disorders [37][38][39][40][41]. In the long run, these psychological repercussions may take a chronic course and lead to high rates of suicidality and low levels of social functioning [42,43].…”
Section: Repercussions Of Childhood Interpersonal Traumamentioning
confidence: 99%
“…Indeed, childhood interpersonal trauma is associated with increased risk of mental health problems throughout the lifespan [44], including posttraumatic stress, eating disorders [45], depression, anxiety, suicidality, and substance use [24,46]. Ultimately, these psychological problems may take a chronic course and lead to low levels of relational and professional functioning, higher rates of suicidality and less active social participation [40,42,43]. Moreover, there appears to be a cumulative effect of exposure to trauma during childhood with the risk of psychological, physical, and relational health problems increasing as the number of different types of victimization experienced increases [31,44,47,48].…”
Section: Psychological Repercussions Of Childhood Interpersonal Traumamentioning
confidence: 99%
“…Recent research has, in fact, suggested that the use of the word 'inheritors' here is surprisingly literal, that the trauma of the Holocaust may be transmitted transgenerationally. This research spans multiple disciplines, including both those in the sciences (see, e.g., Gray et al 2017;Lehrner and Yehuda 2018;Nugent et al 2008;Ramo-Fernández et al 2015;Samuels 2014;Wilker and Kolassa 2012;Yehuda et al 2002Yehuda et al , 2008Yehuda and Bierer 2009), and social sciences (see, e.g., Chaitin 2002;Costa et al 2018;Fromm 2012;Lev-Wiesel 2007;Scharf 2007;Scharf and Mayseless 2011). The dialogue between these different modes of research forms an image of a complicated interrelation of different modes of transmission, from epigenetic modifications transferred via gametes, to the social processes at work when a traumatised parent's behaviour impacts the child's life and world of meaning.…”
Section: Introductionmentioning
confidence: 99%